DOMESTIC VIOLENCE AGAINST PREGNENT WOMEN - Noonart, Tassanee; Lahukarn, Benjawan; Sopa, Nujarat (Journal of Buddhist Anthropology, 2021)
This academic paper aims to recognize The importance of domestic violence which will have an effect on pregnant women and the fetus it can cause injury or death. Effects on pregnancy and delivery include miscarriage. Miscarriage low birth weight babies Placental abruption It is the leading cause of antepartum hemorrhage Causing the maternal mortality rate to increase. In the psychosocial aspect, it was found that the pregnant women had severe psychological trauma. Abnormalities may arise posttraumatic stress disorder, stress, depression leading to drug and substance use. Causing problems in motherhood and parenting or some people feel hurt, shame, feelings of anger, resentment, feeling of betrayal, guilt, worthlessness, confusion in solving problems, lack of dependence, and even suicide. Health workers should be aware of the occurrence of domestic violence. And violence screening is performed in all pregnant women who come to antenatal care. By taking a history wash, it can help detect up to 65 -70% Airway-Breathing-Circulation-Disability (ABCD) respectively. Women set the month to sit on the seat so as not to squeeze on the inferior black vena cava to prevent shock. Doppler ultrasound listens to the baby's heart, in women, requires 6 -24 hours of monitoring. As well as publicize resources to help pregnant women to be safe from harm or from potential impacts And there must be empathy, understanding and acceptance without blaming the pregnant woman might confirm or tolerate the incident.